Vasoplegic syndrome in patients undergoing heart transplantation - Tong-xin Qin; Yun-tai Yao; the Evidence in Cardiovascular Anesthesia(EICA) Group (Frontiers in Surgery, 2023)
ObjectivesTo summarize the risk factors, onset time, and treatment of vasoplegic syndrome in patients undergoing heart transplantation.MethodsThe PubMed, OVID, CNKI, VIP, and WANFANG databases were searched using the terms “vasoplegic syndrome,” “vasoplegia,” “vasodilatory shock,” and “heart transplant*,” to identify eligible studies. Data on patient characteristics, vasoplegic syndrome manifestation, perioperative management, and clinical outcomes were extracted and analyzed.ResultsNine studies enrolling 12 patients (aged from 7 to 69 years) were included. Nine (75%) patients had nonischemic cardiomyopathy, and three (25%) patients had ischemic cardiomyopathy. The onset time of vasoplegic syndrome varied from intraoperatively to 2 weeks postoperatively. Nine (75%) patients developed various complications. All patients were insensitive to vasoactive agents.ConclusionsVasoplegic syndrome can occur at any time during the perioperative period of heart tranplantation, especially after the discontinuation of bypass. Methylene blue, angiotensin II, ascorbic acid, and hydroxocobalamin have been used to treat refractory vasoplegic syndrome.